Phylum EcMmodermata - A source for biologically active compounds: A Review - Ilangakoon, H.P.; Jayasuriya, W.J.A.B.N. (Pharmaceutical Journal of Sri Lanka 2016, 2016)
Attached
Keywords: Echinoderms; Saponins; carotenoids; biologically active compounds